Upaya Meningkatkan Keterampilan Berpikir Kritis IPA Siswa Kelas IV SD Negeri Ciawi III dengan Menggunakan Model Pembelajaran Problem Based Learning (PBL) pada Materi Daun - Destri Manafviani; Ade Maftuh; Rizki Hadiwijaya Zulkarnaen (Lembaga Bale Literasi, 2025)
Critical thinking skills as a reflective and rational thinking process, which is carried out seriously to determine what to believe and what actions to take. This study aims to improve the critical thinking skills of science of grade IV students of Ciawi III Elementary School using the Problem Based Learning (PBL) learning model on leaf material. This study uses a classroom action research (CAR) method with a population of 18 people which is carried out in 2 cycles, namely cycle I and cycle II and is carried out in 3 days, namely Thursday, Monday and Tuesday in March 2025. Data collection techniques used are tests, observations and documentation. The results obtained showed an increase in critical thinking skills by 80% using the Problem Based Learning (PBL) learning model. Therefore, the use of the Problem Based Learning (PBL) learning model has a positive impact on improving the critical thinking skills of elementary school students. The Problem Based Learning (PBL) learning model can be used by teachers as a way to provide broad understanding with the help of learning models.